REGULATION OF POLITICAL PARTIES IN LEGISLATIVE AND PRESIDENTIAL ELECTIONS IN CONSTITUTIONS IN VARIOUS COUNTRIES - Hevi Dwi Oktaviani (HERMENEUTIKA : Jurnal Ilmu Hukum, 2022)
Political parties are organizations that exist as a consequence of a democratic state that is closely related to general elections. Indonesia will hold simultaneous elections in a few years, of course, studies and references are needed that can help perfect the regulation of political parties and elections. The study can be carried out using the constitutional comparison method because most countries regulate the provisions of political parties and elections in the constitution, for example in Indonesia it is regulated in the 1945 Constitution. The purpose of this study is to determine the arrangement of political parties in elections based on the constitution in each country. The results of the research are expected to be used as an academic reference regarding the regulation of political parties and elections in Indonesia. The research method used is normative legal research by utilizing primary and secondary legal materials which are then analyzed qualitatively. The author uses the constitutions of 42 countries in the world. The results of the study show that political parties are still institutions that are trusted as parties that have the right to submit candidates for legislative and presidential candidates in many countries. There are still more countries that give political parties the exclusive right to nominate such candidates than countries that allow independent candidates.